Rural development and planning perspectives: proceeding of a National Seminar - Naidu, K. Munirathna (ed.) (New Delhi, 1992)
The book reveals the significance of grass roots level planning for promoting rural development in India. Indian planning. techniques and approaches have been chang ing suiting to the requirements of areas and times, though slowly. Macro approach adopted since first five year plan in India has allowed state plans to introduce spatial planning through decentralised technique during Seven Five Year Plan. All the states in India have adopted this technique through District Planning and Zilla Parishad and Panchayat Raj model. In other words Micro approach to planning has been initiated during Seventh Five Year Planning to promote rural growth and prosperity with the aim of distri buting the same equitably amongst the people, classes and area for achieving justice. Govern ment of India initiated this new experiment and technique to remove poverty and eliminate regional imbalanced and inequalities in a scientific way. It is with this new objective government has allocated fifty percent of plan. out-lay for rural development during eighth five year plan. In this context grass roots level planning for rural development assumes added relevance.. The book attempts experiences of States on the path of rural development through grass roots level planning, printing out the defects in plan formulation and implementation at lower levels and areas and provided valuable suggestions for their removal in the interest of balanced rural growth. The book proves that Panchayat system acts formulated not inimical to democracy; it is not intended to decentralise corruption, but bring about cooperation to eliminate corruption if any for total growth. As Mahatma Gandhi ji aptly remarked in a letter to Pandit Jawaharlal Nehru) that man is not born to live aline; he is a social being living both independently and in co-operation with others. To bring about change in line with such atmosphere, as a measure of society, one should take a village as a unit. It becomes a standard and self sustaining unit. This idea is amply proved in this book by the attempts made by states through grass roots level planning for achieving rural development. It discussed these aspects through four sections
Keywords: Rural Development